BAT117213: Ileal bile acid transporter (IBAT) inhibition as a treatment for pruritus in primary biliary cirrhosis: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Hegade, Vinod; Kendrick, Stuart; Dobbins, Robert; Miller, Sam; Richards, Duncan; Storey, James; Dukes, George; Gilchrist, Kim; Vallow, Susan; Alexander, Graeme; Corrigan, Margaret; Hirschfield, Gideon; et al.
Abstract Background Pruritus (itch) is a symptom commonly experienced by patients with cholestatic liver diseases such as primary biliary cholangitis (PBC, previously referred to as primary biliary cirrhosis). Bile acids (BAs) have been proposed as potential pruritogens in PBC. The ileal bile acid transporter (IBAT) protein expressed in the distal ileum plays a key role in the enterohepatic circulation of BAs. Pharmacological inhibition of IBAT with GSK2330672 may reduce BA levels in the systemic circulation and improve pruritus. Methods This clinical study (BAT117213 study) is sponsored by GlaxoSmithKline (GSK) with associated exploratory studies supported by the National Institute for Health Research (NIHR). It is a phase 2a, multi-centre, randomised, double bind, placebo controlled, cross-over trial for PBC patients with pruritus. The primary objective is to investigate the safety and tolerability of repeat doses of GSK2330672, and explore whether GSK2330672 administration for 14 days improves pruritus compared with placebo. The key outcomes include improvement in pruritus scores evaluated on a numerical rating scale and other PBC symptoms in an electronic diary completed twice daily by the patients. The secondary outcomes include the evaluation of the effect of GSK2330672 on total serum bile acid (BA) concentrations, serum markers of BA synthesis and steady-state pharmacokinetics of ursodeoxycholic acid (UDCA). Discussion BAT117213 study is the first randomised controlled crossover trial of ileal bile acid transporter inhibitor, a novel class of drug to treat pruritus in PBC. The main strengths of the trial are utility of a novel, study specific, electronic symptom diary as patient reported outcome to measure the treatment response objectively and the crossover design that allows estimating the treatment effect in a smaller number of patients. The outcome of this trial will inform the trial design of future development phase of the IBAT inhibitor drug. The trial will also provide opportunity to conduct metabonomic and gut microbiome studies as explorative and mechanistic research in patients with cholestatic pruritus. Trial registration EudraCT number: 2012-005531-84, ClinicalTrials.gov Identifier:NCT01899703, registered on 3rd July 2013